2020
DOI: 10.1186/s12876-020-01204-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity intervention for non-diabetic patients with non-alcoholic fatty liver disease: a meta-analysis of randomized controlled trials

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disease nowadays. Changes in diet and lifestyle have led to a dramatic increase in the prevalence of NAFLD around the world. This meta-analysis is to investigate the efficacy of physical activity intervention on liver-specific endpoints in the population with NAFLD, including hepatic enzyme, serum lipid, glucose metabolism and intra-hepatic lipid. Methods: PubMed and China National Knowledge Infrastructure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
6
29
0
3
Order By: Relevance
“…As far as we know, this study is the first to analyze the effects of different exercise modes on blood biochemical indexes (TG, TC, LDL, and HDL), liver function related enzymes (ALT, AST, and GGT), and BMI in patients with NAFLD. This meta-analysis showed that aerobic exercise and resistance exercise can significantly improve TG and AST in patients with NAFLD, which is consistent with a recent study [ 30 ]. Aerobic exercise and HIIT can significantly reduce ALT in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, this study is the first to analyze the effects of different exercise modes on blood biochemical indexes (TG, TC, LDL, and HDL), liver function related enzymes (ALT, AST, and GGT), and BMI in patients with NAFLD. This meta-analysis showed that aerobic exercise and resistance exercise can significantly improve TG and AST in patients with NAFLD, which is consistent with a recent study [ 30 ]. Aerobic exercise and HIIT can significantly reduce ALT in patients with NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, although combining an exercise program with dietary interventions augments the reduction in hepatic fat content, exercise only is also effective in reducing hepatic lipid content in NAFLD patients [136,146]. As most of the studies have been performed with diabetic and/or obese NAFLD patients, the beneficial effect of exercise still needs confirmation in large-scale prospective studies, as a recent meta-analysis showed that physical activity only slightly reduces liver fat content in non-diabetic NAFLD patients [147]. Interestingly, starting to exercise has been independently associated with NAFLD remission only in men, suggesting a sex-specific hepatic response to exercise [148].…”
Section: Exercisementioning
confidence: 99%
“…Meta-analyses in adult population with NAFLD clearly showed that exercise alone has a large effect on IHTG levels, which remains significant even in the absence of weight loss [56,57]. Both aerobic [58] and resistance exercise [59], compared to usual care or their combination [43], are shown to improve IHTG or other glucose metabolic indices, such as HOMA-IR and HbA1C, while no clear superiority of aerobic exercise over resistance exercise exists [60,61].…”
Section: Discussionmentioning
confidence: 99%